Magnetic flux surfaces by the fractional Heisenberg antiferromagnetic flow of magnetic b-lines in binormal direction in Minkowski space - Koerpinar, Talat; Asil, Vedat; Koerpinar, Zeliha; Demirkol, Ridvan Cem (Elsevier, 2022)
In this manuscript, we first compute Lorentz equations with magnetic b-lines in binormal direction in Minkowski space based on novel studies of evolution for magnetic particles. Then, we further calculate the fractional flow equations for magnetic b-lines with inextensible Heisenberg optical antiferromagnetic flow in Minkowski space. Thus, we determine optical soliton surface related with inextensible Heisenberg optical antiferromagnetic flow in Minkowski space. Later, we consider the corresponding magnetic and geometric quantities to describe necessary and sufficient conditions that have to be satisfied by magnetic optical flux surfaces of inextensible Heisenberg optical antiferromagnetic model.
Keywords: Magnetic field lines; Geometric phase; Magnetic flux surface; Heisenberg optical antiferromagnetic flow; Lorentz force